2016
DOI: 10.1016/j.pvr.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

HPV vaccination initiation after the routine-recommended ages of 11–12 in the United States

Abstract: BackgroundSince 2006, routine HPV vaccination has been recommended for females aged 11–12 in the US. However not much is known about the extent of and factors associated with HPV vaccination after the ages of 11–12.MethodsProvider-verified data on 8710 females aged 13–17 were analyzed from the 2013 NIS-Teen survey. 2013 Data was utilized since it was the first year one can fully evaluate the age at vaccination through age 17 for females who could receive the HPV vaccine at age 11.ResultsAmong HPV vaccinated fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…We selected covariates based on bivariate analyses and literature supporting the association of each of these factors with HPV initiation. These included: daughter’s age (continuous), daughter’s health insurance status (uninsured, public, or private, insurance), mother’s age (continuous), and household income (dichotomized as no income to $14,999 vs. >$15,000) [25,36,37]. Because data were obtained from a group-randomized control trial testing the impact of an intervention, we dummy coded study arm to include as a covariate in the models with vaccination status as the outcome.…”
Section: Methodsmentioning
confidence: 99%
“…We selected covariates based on bivariate analyses and literature supporting the association of each of these factors with HPV initiation. These included: daughter’s age (continuous), daughter’s health insurance status (uninsured, public, or private, insurance), mother’s age (continuous), and household income (dichotomized as no income to $14,999 vs. >$15,000) [25,36,37]. Because data were obtained from a group-randomized control trial testing the impact of an intervention, we dummy coded study arm to include as a covariate in the models with vaccination status as the outcome.…”
Section: Methodsmentioning
confidence: 99%
“…As an example, let us examine the HPV vaccine to demonstrate the potential benefits. According to the 2013 NIS‐Teen survey, the HPV vaccine in the United States has been administered (at least first dose) to only 47% of female adolescents (95% CI = 43%–50%) after age 12 and many of these young women do not complete the three dose protocol (Beachler, Gonzales, Kobrin, & Kreimer, ). In this survey, series completion by young men was only 13.9%.…”
mentioning
confidence: 99%
“…For this reason, advisory committees in most developed countries, including the US, recommend routine vaccination of pre-teen boys and girls (aged 11-12 years) to avoid the challenge of predicting sexual initiation, which is rare before these ages in the US (Cavazos-Rehg et al, 2009;Finer and Philbin, 2013;Petrosky et al, 2015). Despite this recommendation, roughly half of girls vaccinated against HPV in the US reported receiving their first dose after age 12, and nearly a quarter received it after age 15 (Beachler et al, 2016).…”
mentioning
confidence: 99%
“…It was suggested that administering the HPV vaccine simultaneously with these vaccines would increase the likelihood that a child would be fully vaccinated by the appropriate age (Markowitz et al, 2007), which is the case for other vaccines administered concomitantly (National Vaccine Advisory Committee, 2003). However, compared with Tdap and Meningococcal vaccines, a recent study found that US girls were less likely to receive one or more doses of the HPV vaccine by age 12; and while 90% of those vaccinated against HPV had also received both the Tdap and Meningococcal vaccines, fewer girls who received either the Tdap or Meningococcal vaccine had been vaccinated against HPV (61% and 67%, respectively) (Beachler et al, 2016). Another theoretical concern is that if the recommended target age were to be lowered at this point (10 years post-introduction), some clinicians and parents may continue to consider any time before age 12 acceptable for vaccine initiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation